Nuclear and cytoplasmic huntingtin inclusions exhibit distinct biochemical composition, interactome and ultrastructural properties - Riguet, Nathan; Mahul-Mellier, Anne-Laure; Maharjan, Niran; Burtscher, Johannes; Croisier, Marie; Knott, Graham; Hastings, Janna; Patin, Alice; Reiterer, Veronika; Farhan, Hesso; Nasarov, Sergey; Lashuel, Hilal A. (Nature communications, 2021)
Despite the strong evidence linking the aggregation of the Huntingtin protein (Htt) to the pathogenesis of Huntington’s disease (HD), the mechanisms underlying Htt aggregation and neurodegeneration remain poorly understood. Herein, we investigated the ultrastructural properties and protein composition of Htt cytoplasmic and nuclear inclusions in mammalian cells and primary neurons overexpressing mutant exon1 of the Htt protein. Our findings provide unique insight into the ultrastructural properties of cytoplasmic and nuclear Htt inclusions and their mechanisms of formation. We show that Htt inclusion formation and maturation are complex processes that, although initially driven by polyQ-dependent Htt aggregation, also involve the polyQ and PRD domain-dependent sequestration of lipids and cytoplasmic and cytoskeletal proteins related to HD dysregulated pathways; the recruitment and accumulation of remodeled or dysfunctional membranous organelles, and the impairment of the protein quality control and degradation machinery. We also show that nuclear and cytoplasmic Htt inclusions exhibit distinct biochemical compositions and ultrastructural properties, suggesting different mechanisms of aggregation and toxicity. The mechanisms underlying Huntingtin protein (Htt) aggregation are not fully understood. Here the authors perform a detailed investigation of the ultrastructural and biochemical properties of huntingtin cytoplasmic and nuclear inclusions, and reveal that they form via distinct mechanisms and exert their toxicity via different pathways.